2019
DOI: 10.35800/akulturasi.7.1.2019.24394
|View full text |Cite
|
Sign up to set email alerts
|

Strategi Agrobisnis Budidaya Rumput Laut Di Desa Buku Utara Kecamatan Belang Kabupaten Minahasa Tenggara Provinsi Sulawesi Utara

Abstract: AbstrakKKP telah menetapkan antara lain menerapkan prinsip-prinsip pengelolaan sumberdaya kelautan dan perikanan yang bertanggung jawab, berdaya saing, dan berkelanjutan. Salah satu langkah operasional yang perlu dilakukan adalah mengembangkan budidaya rumput laut. Tujuan  penelitian ini untuk mengetahui strategi agrobisnis budidaya rumput laut di Desa Buku Utara Kecamatan Belang Kabupaten Minahasa Tenggara Provinsi Sulawesi Utara. Metode penelitian yang digunakan adalah studi kasus, dengan cara mempelajari/me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Next [6]; [7]; [8]; [9]; Aquaculture and has unlimited export market opportunities. The development of seaweed cultivation can contribute to reducing unemployment, alleviating poverty, and economic growth.…”
Section: Figure1 Map Of Alor County Administrative Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next [6]; [7]; [8]; [9]; Aquaculture and has unlimited export market opportunities. The development of seaweed cultivation can contribute to reducing unemployment, alleviating poverty, and economic growth.…”
Section: Figure1 Map Of Alor County Administrative Regionmentioning
confidence: 99%
“…Based on the results of observations and interviews with farmers showed that the identification/mapping of the parties in the seaweed marketing chain in two villages and also in some areas in Alor Regency is as follows: (1) produce is a farmer who conducts seaweed cultivation business around the coast (coastal). The land used to cultivate seaweed is the high seas controlled by the state, so farmers only have the right to use it according to the statement [21]; [22]; [6]; [23]; [24]; [25]; [26]; [27], The land limit used corresponds to the number of rope stretches owned by each farmer and the land tenure is not permanently owned but only controlled as long as they carry out cultivation activities. The production of seaweed harvested is partly used as re-seedlings and some dried to be sold to traders.…”
Section: Identification Of Parties In the Marketing Chainmentioning
confidence: 99%